Strategi Prioritas dalam Menanggulangi Dampak Pandemi COVID-19 terhadap Kondisi Sosial Ekonomi Masyarakat Nelayan di Pantai Sanur - SARI, RUTH MAWAR; AMBARAWATI, I GUSTI AGUNG AYU; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Priority Strategy to Overcome the Impact of COVID-19 Pandemic Towards Socio-Economic Conditions of the Fisherman Communities at Sanur Beach.  A fisherman is someone who makes a living from catching marine products. The COVID-19 pandemic has an impact on all fields, including marine and fisheries. The purposes of this research were to determine the impact of the COVID-19 pandemic on socio-economic conditions and priority strategies in overcoming the obstacles faced. The data used is primary data by doing a survey to 74 respondents who are members of fishing groups in Sanur who have legal entities, make fishing profession before and during the COVID-19 pandemic. The analysis techniques used were qualitative descriptive and Interpretive Structural Modeling. The results of the study show that the main obstacles faced by fisherman are communication, competition and marketing institutions. The strategy to overcome these obstacles is to hold meetings with the Regional Office of Marine Affairs and Fisheries, counseling to reduce competition for catches, increasing marketing agencies to receive catches. The suggestions put forward to Regional Office of Maritime Affairs and Fisheries are routine assistance and counseling on applications and technology, equitable distribution of aids, procurement of subsidies fuel and increasing the number of marketing institutions and for fishermen to innovate their business by utilizing information and technology they have.